BACKGROUND TO THE EMERGENCE OF THE SOCIAL AND COOPERATIVE ECONOMY IN CHILE BETWEEN THE 19TH AND 20TH CENTURIES. SOME CLUES FOR ITS RECONSTRUCTION AND INTERPRETATION; ANTECEDENTES DEL SURGIMIENTO DE LA ECONOMÍA SOCIAL Y COOPERATIVA EN CHILE ENTRE EL SIGLO XIX Y XX. ALGUNAS PISTAS PARA SU RECONSTRUCCIÓN E INTERPRETACIÓN - Radrigan-Rubio, M (Faculty of Legal Sciences and Labor, University of Vigo, 2025)
This article presents an overview of the academic and political debate on this topic, revealing a wide diversity of actors and approaches, both from the perspectives of social leaders promoting initiatives within the social and cooperative economy, especially those linked to the worker-craft sector, as well as from various political and intellectual leaders. This allows us to appreciate an interesting public debate in the context of the turn of the century, marked in Chile by a high level of social conflict known as the “Social Question.”. © 2025, Faculty of Legal Sciences and Labor, University of Vigo. All rights reserved.